HUBUNGAN ANTARA FUNGSI KOGNITIF DENGAN KESEIMBANGAN DAN PERFROMA FISIK PADA LANJUT USIA DI PUSKESMAS TURIKALE - Hikmah, Nurul; Andi Rahmaniar SP; Hamisah (Indonesian Journal of Physiotherapy, 2023)
Someone who has entered the age of 60 and over or often called elderly will experience damage and loss of function in organ systems gradually so that they are susceptible to health problems, cognitive function disorders. Decreased motor response and perception due to decreased cognitive function can cause balance disorders that affect physical performance in the elderly. This study aims to determine the relationship between cognitive function and balance and physical performance in the elderly at the Turikale Health Center. This research is a quantitative study with a cross sectional approach. Respondents from this study were 127 elderly people aged 60 years and over who met the inclusion criteria. Based on the results of the Spearman's Rho correlation test, the significance value (p) of the cognitive function variable was obtained with a balance of 0.003 (p <0.05), while the correlation of cognitive function and physical performance shows that the significance value (p) is 0.193 (p>0.05) The results of the study showed that there was a relationship between cognitive function and balance in the elderly at the Turikale Health Center, but there was no significant relationship between cognitive function and physical performance. Keywords: Cognitive Function; Balance; Aging; Physical Performance